Caracterización de actividades constructivas basado en conceptos de mejoramiento de productividad y desarrollo de procedimientos técnicos (2020)
This document shows a comparison among concepts of productivity enhance related to constructive activities procedures and an interview with a project manager in a construction loctaed in Bogota. Exposing step by step de execution of the procedures and the productive enhance concepts.2